Patterns and processes in complex landscapes: testing alternative biogeographical hypotheses through integrated analysis of phylogeography and community ecology in Hawai'i. Issue 13 (17th May 2013) - Eldon, Jon; Price, Jonathan P.; Magnacca, Karl; Price, Donald K.
Abstract The Island of Hawai'i is a dynamic assemblage of five volcanoes with wet forest habitat currently existing in four distinct natural regions that vary in area, age and geographical isolation. In this complex landscape, alternative assumptions of the relative importance of specific habitat characteristics on evolutionary and ecological processes predict strikingly different general patterns of local diversity and regional similarity. In this study, we compare alternative a priori hypotheses against observed patterns within two distinct biological systems and scales: community composition of wet forest vascular plant species and mitochondrial and nuclear genes of Drosophila sproati, a wet‐forest‐restricted endemic. All observed patterns display strong and similar regional structuring, with the greatest local diversity found in Kohala and the windward side of Mauna Loa, the least in Ka'ū and Kona, and a distinctive pattern of regional similarity that probably reflects the historical development of this habitat on the island. These observations largely corroborate a biogeographical model that integrates multiple lines of evidence, including climatic reconstruction, over those relying on single measures, such as current habitat configuration or substrate age. This method of testing alternative hypotheses across biological systems and scales is an innovative approach for understanding complex landscapes and should prove valuable in diverse biogeographical systems.